Hydroxysafflor yellow A promotes α-synuclein clearance via regulating autophagy in rotenone-induced Parkinson’s disease mice - Han, Bing; Wang, Lijie; Fu, Fenghua; Wang, Zhenhua; Zhang, Leiming; Qi, Grace Jia; Wang, Tian (Folia Neuropathologica, 2018)
Autophagy is an intracellular degradation process that is involved in α-synuclein (α-syn) homeostasis and Parkinson’s disease (PD). The purpose of this study was to investigate whether hydroxysafflor yellow A (HSYA) could promote α-syn clearance via regulating autophagy in PD mice. Male C57BL/6 mice were intraperitoneally treated with HSYA. Thirty minutes later, they were intragastrically administered with rotenone at a dose of 30 mg/kg. The hanging wire test was performed at 14 and 28 days. Then, autophagosomes and ultrastructural changes were examined by transmission electron microscopy. The expression of tyrosine hydroxylase (TH), α-syn, JNK1, p-JNK1, Bcl-2, p-Bcl-2, Beclin1, autophagy-related proteins (Atg) 7 and 12-5, and the LC3-II/LC3-I ratio were investigated by western blot. The hanging time of HSYA-treated PD mice was significantly increased compared with that of rotenone-induced PD mice (p < 0.05 or p < 0.01). Compared with rotenone-induced PD mice, treatment with HSYA augmented the formation of autophagosomes. The expression of TH, p-JNK1/JNK1, Beclin1, Atg7, Atg12-5, p-Bcl-2/Bcl-2, and the LC3-II/LC3-I ratio were significantly increased, whereas the expression of α-syn was reduced in the rotenone plus HSYA group. These results indicate that HSYA promoted α-syn clearance via regulating autophagy in rotenone-induced PD mice.